If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4 + -3x) + 17 = -3(7 + 8x) + -7 (4 * 5 + -3x * 5) + 17 = -3(7 + 8x) + -7 (20 + -15x) + 17 = -3(7 + 8x) + -7 Reorder the terms: 20 + 17 + -15x = -3(7 + 8x) + -7 Combine like terms: 20 + 17 = 37 37 + -15x = -3(7 + 8x) + -7 37 + -15x = (7 * -3 + 8x * -3) + -7 37 + -15x = (-21 + -24x) + -7 Reorder the terms: 37 + -15x = -21 + -7 + -24x Combine like terms: -21 + -7 = -28 37 + -15x = -28 + -24x Solving 37 + -15x = -28 + -24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24x' to each side of the equation. 37 + -15x + 24x = -28 + -24x + 24x Combine like terms: -15x + 24x = 9x 37 + 9x = -28 + -24x + 24x Combine like terms: -24x + 24x = 0 37 + 9x = -28 + 0 37 + 9x = -28 Add '-37' to each side of the equation. 37 + -37 + 9x = -28 + -37 Combine like terms: 37 + -37 = 0 0 + 9x = -28 + -37 9x = -28 + -37 Combine like terms: -28 + -37 = -65 9x = -65 Divide each side by '9'. x = -7.222222222 Simplifying x = -7.222222222
| -2(2)-y=11 | | -4(0)-y=12 | | (24x+2)+4=46 | | 12(0)-2y=-14 | | (26x+3)+56=45 | | -24(0)-3y=1 | | -3-4y=-5 | | -2(-4.5)+2y=-10 | | 7(-4)-4y=-16 | | (12c^10)/(4c^14) | | 4(0)+2y=-4 | | x-4/5=-1/5 | | (10c^10)/(4c^14) | | .075=(.075)x^2+(29.43) | | C+(4-3c)=0 | | -8(0)-2y=-2 | | 5x-20+3x+30=7x+20 | | 12c^10/4c^14 | | 7x-4(-2x-11)=-16 | | 12c^10/4c14 | | 4x+2(-2x-1)=-4 | | 8x^2-36x+36=25 | | -x-(-5x+4)=4 | | -8x-2(-4x+1)=-2 | | -4x-7(6x+4)=18 | | -4x-(-4x+8)=-3 | | 7(t-3)=2(t-9)+2r | | 6a-11a=7 | | -2x+4(3x)=-10 | | 2x+4+5x+10+3x=84 | | 121x^2+169=0 | | -5x-4(2x+4)=23 |